Child Sexual Abuse in the Roman Catholic Church in France: Prevalence and Comparison With Other Social Spheres - Bajos, Nathalie (Journal of interpersonal violence, 2023)
This study aims to estimate and compare Roman Catholic Church-related child sexual abuse (CSA) prevalence and characteristics to CSA in other social spheres in France since 1950. Using a cross-sectional representative web-based survey of 28,026 adults in 2021, the weighted prevalence of CSA was estimated according to six social spheres of perpetration: family, Church, school, sports club, artistic activities, and summer camps. Altogether, 14.60%, 95% confidence interval [CI: 13.41; 15.80] of female respondents and 6.38% [5.73; 7.03] of male respondents had experienced CSA. Family was the most common social sphere of perpetration (3.55% [3.18; 3.92]), followed by the Church (0.81% [0.62; 0.99] of respondents exposed) and public schools (0.32% [0.23; 0.40] of respondents exposed). Altogether, we estimate 213,000, 95% CI [147,000; 278,000] people were victims of Church CSA since 1950 in France. Church CSA was more common among men than women (1.28% [0.93; 1.64] vs. 0.34% [0.20; 0.48]) while the opposite was true for other social spheres. CSA was overwhelmingly perpetrated by men ranging from 93.37% in the Church to 97.65% in schools. Many victims spoke with someone about these abuses: 41.81% of the Catholic Church compared to 41.25% of school CSA victims and 51.68% of family CSA victims. Results suggest structural factors including gender norms, but also the spiritual authority of the priest and the culture of secrecy contribute to clerical CSA.